2007
DOI: 10.1111/j.1528-1167.2007.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical treatment of insular epilepsy with nocturnal hypermotor seizures

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 13 publications
1
44
0
1
Order By: Relevance
“…data]. Unlike past studies, 28 more recent publications suggest that insular epilepsy surgery can be both safe and beneficial when performed with modern microsurgical techniques [8,29,30,31,32,33,34]. Still, surgery in the insular region remains a challenge because of the risk of injury to the surrounding highly functional opercula, the numerous arteries transiting on the surface of the insula, and deeper structures (such as the arcuate fasciculus, basal ganglia and internal capsule) [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…data]. Unlike past studies, 28 more recent publications suggest that insular epilepsy surgery can be both safe and beneficial when performed with modern microsurgical techniques [8,29,30,31,32,33,34]. Still, surgery in the insular region remains a challenge because of the risk of injury to the surrounding highly functional opercula, the numerous arteries transiting on the surface of the insula, and deeper structures (such as the arcuate fasciculus, basal ganglia and internal capsule) [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative and postoperative MRI show that the remnant insular cortex was completely removed using subpial depth electrodes (c, d) [17]. Also, non-lesional patients with insular seizure onset and nocturnal hypermotor seizure have successfully undergone epilepsy surgery [6].…”
Section: Insular Surgerymentioning
confidence: 99%
“…In recent years it has been shown that sleep-related complex motor attacks, similar to those occurring in NFLE patients, may also originate from the temporal lobe [8,71,72,81], the insular-opercular region [9, 65•, 84••, 85,86], and the posterior cerebral regions [65•]. A careful analysis of aura features may be particularly useful in the differential diagnosis of NFLE.…”
Section: Clinical Features Of Nflementioning
confidence: 99%